Hubungan Tingkat Pengetahuan Ibu tentang Gizi Balita dengan Status Gizi Balita Berdasarkan Indeks Tinggi Badan Menurut Umur - Ignasia Nila, Siwi; Rofifah, Nuurur; Widyaningrum, Rahmah (Jurnal Keperawatan Mandira Cendikia, 2022)
Nutritional status of toddler is still a special concern in various countries, especially the problem of stunting. Stunting is a condition in which children are shorter in height than their age. In addition, children with stunting have several other characteristics such as; slowed growth, poor cognitive performance, signs of delayed puberty, becomes quiet at the age of 8-10 years, and the face looks younger than his age. Stunting has an impact in the form of impaired physical growth, impaired brain development, and impaired body metabolism which in the long term can reduce a person's cognitive abilities and immunity. The purpose of this research is to determine the relationship between mother's level of knowledge about under-five nutrition with under-five nutritional status based on height index by age. This research is a correlational observational study with a cross sectional approach. The sample of this study amounted to 49 mothers who have toddlers aged 25-59 months and registered at the Posyandu Desa Padas. The sampling technique used is purposive sampling technique. The instrument used in this study was a questionnaire on the mother's level of knowledge about under-five nutrition. The use of statistical tests in this study using Kendall's tau_b. The results of the Kendall's tau_b analysis test obtained the value of Sig. (2-tailed) is 0.149. The results of this study indicate that the relationship between the variable level of mother's knowledge about toddler nutrition and the nutritional status of infants based on the TB/U index is not significant. The unproven hypothesis proposed by the researcher may be caused by the limitations of the researcher in controlling confounding factors. Confounding factors that cannot be controlled by researchers include; information/mass media, experience, food intake of toddlers, limited number of respondents, inaccurate selection of questionnaires both in terms of content and language as well as factors of mother's free time which were not examined by researchers.